The Relationship Between Bank Loans And Economic Growth In Turkey: 1995-2010 - Zortuk, Mahmut; Çeli̇k, Yunus (Alphanumeric Journal, 2015)
In this study, we aim to determine the direction of the relationship between the economic growth and total credits of Turkish Banks. Accordingly, we analyzed this relationship for the period 1995-2010, by using quarterly data analysis. In the analyses as variables, change in the volume of real credits to represent the variable, total credits; and real growth in GDP represents the variable, growth. This study uses Unit Root Test and Gregory-Hansen (GH) Cointegration test as econometric methods. As a result of the analysis and evaluations, it was found that there exists a cointegrating relationship between relevant variables.
Keywords: Araştırma ve Yönetim Bilimi; Banka Kredileri (BK); Ekonomik Büyüme (EB); Zivot- Andrews Birim KökTesti (zabt); Gregory-Hansen (GH) Eşbütünleşme testi; İşletme; Bank Loan (BL); Economic Growth (EG); Zivot- Andrews Breakpoint Test (ZABT); Gregory-Hansen(GH) Cointegration test; İstatistik ve Olasılık; Yöneylem; İktisat; 8. Economic growth; 1. No poverty